VARIATION OF POLYETHYLENE AND POLYPROPYLENE ON THE QUALITY OF PLASTIC TYPES - Ken Ima Damayanti; Dandi Ramdhani; Fajar Ramadhan; Gilang Eka Setiawan (Analit : Analytical and Environmental Chemistry, 2024)
Polyethylene (PE) and polypropylene (PP) provide different characteristics to the produced plastics. The focus of this research is to identify the influence of variations in the composition of polyethylene and polypropylene to produce a new polymer blend with strong mechanical properties and resistance to breaking. Quality parameters observed include tensile strength and flexural modulus tests, notched Izod impact, hardness, and Fourier Transform Infrared Spectroscopy (FTIR). It has been found that the PP:PE (80:20) produces plastic with strong mechanical characteristics while being less prone to breakage, thus making it suitable for plasticware materials.